Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2026)
This edition of NIU Journal of Social Sciences focuses on Development Administration and Social Psychology. The first part of the Journal addresses issues in Development Administration such as Sustainable Development, Pentecostal Entrepreneurship, Community Development, Service Charge Administration, Public Bureacracy, Human Security and Entrepreneurship Education. It is emphasized in one of the papers that service charge governance failures stem from systemic rather than isolated deficiencies, encompassing weak information disclosure, inadequate administrative systems, operational limitations, and regulatory fragmentation. It is therefore, suggested that structured governance reforms including digital accounting systems, utility metering, formal reserve funds, tenant engagement structures, and standardized regulatory frameworks should be put in place to address interconnected governance deficiencies in commercial property management. Papers in the second part are on Social Pyschology. It is revealed in one of the papers in this section that eventhough hierarchy influences authority in the academic workplace, social capital creates the conditions for cooperation. The study therefore, recommends structured mentoring, more inclusive committee systems, and deliberate trust-building efforts to strengthen collaboration across generations. Readers are advised to make proper use of the ideas presented by the various authors in this issue of NIU Journal of Social Sciences. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them.